The prevalence of work-related respiratory disease among dairy farmers - N. A. Athirah, .; A. A., Suhaimi (Penerbit Universiti Malaysia Pahang, 2024)
Work-related respiratory disease is very common among dairy farming sectors. The respiratory problems and symptoms have been assessed using a validated respiratory health status questionnaire in 85 dairy farmers. This study involves a cross-sectional study design where descriptive analysis is being used to determine the prevalence of respiratory disease using frequency and the chi square test of independence was performed to determine the relationship between respiratory disease and work practices. Respiratory diseases with the highest prevalence include tuberculosis (31.8%) and asthma (8.2%). The most common respiratory disease symptoms among dairy farmers are productive cough (40.0%) and wheeze (21.2%). There is no correlation between the length of time dairy farmers worked and the feeding approach they employed and work-related respiratory disease. A significant frequency of respiratory difficulties is still experienced by dairy farmers. Although the precise cause is still unidentified but, it may be connected to extended exposure to dust during work.